Систематична структура ценофлор класів піонерної рослинності України - Дубина, Д.В.; Дворецький, Т.В.; Ємельянова, С.М.; Дзюба, Т.П.; Тимошенко, П.А. (Український ботанічний журнал, 2017)
Проаналізовано систематичну структуру флори новоутворених екотопів, яка нараховує 1690 видів судинних рослин, що належать до 104 родин і 584 родів, і ценофлору класів піонерної рослинності України, репрезентовану 844 видами із 80 родин і 338 родів. Установлено, що подібність флор обох груп за коефіцієнтом Жаккара складає 0,28. Переважна більшість видів флори новоутворених екотопів України та ценофлор класів піонерної рослинності належить до відділу Magnoliophyta. Судинні спорові та голонасінні в обох групах відіграють незначну роль. Десять провідних родин, до яких належать Asteraceae, Poaceae, Brassicaceae, Fabaceae, Caryophyllaceae, Chenopodiaceae, Lamiaceae, Apiaceae, Scrophulariaceae i Polygonaceae, об'єднують 63,2% видів на новоутворених екотопах та 66,3% – у піонерних угрупованнях. Подано аналіз родинних спектрів за класами піонерної рослинності. Встановлено флористичні співвідношення, які вказують на молодий історичний вік відповідних флор та відображають своєрідність фізико-географічного середовища, зокрема високу флуктуаційну активність екологічних процесів. Досліджено аборигенну фракцію, яка нараховує 560 видів, що належать до 252 родів та 70 родин. Проаналізовано подібність видового складу флори новоутворених екотопів, ценофлор класів піонерної рослинності та їхніх аборигенних фракцій за коефіцієнтом Жаккара. Проанализирована систематическая структура флоры новообразованных экотопов, которая насчитывает 1690 видов сосудистых растений, относящихся к 104 семействам и 584 родам, и ценофлор классов пионерной растительности Украины, представленной 844 видами из 80 семейств и 338 родов. Установлено, что сходство обеих групп по коэффициенту Жаккара составляет 0,28. Подавляющее большинство видов флоры новообразованных экотопов Украины и ценофлор классов пионерной растительности относится к отделу Magnoliophyta. Сосудистые споровые и голосеменные в обеих группах играют незначительную роль. Десять ведущих семейств, к которым относятся Asteraceae, Poaceae, Brassicaceae, Fabaceae, Caryophyllaceae, Chenopodiaceae, Lamiaceae, Apiaceae, Scrophulariaceae и Polygonaceae, объединяют 63,2% видов на новообразованных экотопах и 66,3% – в пионерных сообществах. Дается анализ спектров ведущих семейств по классам пионерной растительности. Установлены флористические соотношения, которые указывают на молодой исторический возраст соответствующих флор и отражают своеобразие физико-географической среды, в частности высокую флуктуационную активность экологических процессов. Исследована аборигенная фракция, которая насчитывает 560 видов из 252 родов и 70 семейств. Проанализированы сходство видового состава флоры новообразованных экотопов, ценофлор классов пионерной растительности и их аборигенных фракций по коэффициенту Жаккара. Taxonomic structure of the flora of newly formed habitats (represented by 1690 species of 584 genera from 104 families) and coenofloras of the classes of pioneer vegetation of Ukraine (844 species of 338 genera from 80 families) was analyzed. It has been found that similarity of both groups according to Jaccard index is 0.28. The majority of species of the flora of newly formed habitats and coenofloras of the classes of pioneer vegetation in Ukraine belong to Magnoliophyta. Vascular spore and gymnosperm plants in both groups are less significant. Ten leading families (Asteraceae, Poaceae, Brassicaceae, Fabaceae, Caryophyllaceae, Chenopodiaceae, Lamiaceae, Apiaceae, Scrophulariaceae and Polygonaceae) include 63.2% of species in newly formed habitats and 66.3% in pioneer plant communities. The family spectra of the pioneer vegetation classes were analyzed. The floristic proportions were established, which indicate that both floras are historically young and represent physical and geographical pecularities of the environmental conditions as well as high fluctuation activity of ecological processes. The aboriginal fraction was studied; it contains 560 species of 252 genera from 70 families. Similarity of the species composition of the newly formed habitats, coenofloras of the classes of pioneer vegetation and their aboriginal fractions has been analyzed according to Jaccard index.Taxonomic structure of the flora of newly formed habitats (represented by 1690 species of 584 genera from 104 families) and coenofloras of the classes of pioneer vegetation of Ukraine (844 species of 338 genera from 80 families) was analyzed. It has been found that similarity of both groups according to Jaccard index is 0.28. The majority of species of the flora of newly formed habitats and coenofloras of the classes of pioneer vegetation in Ukraine belong to Magnoliophyta. Vascular spore and gymnosperm plants in both groups are less significant. Ten leading families (Asteraceae, Poaceae, Brassicaceae, Fabaceae, Caryophyllaceae, Chenopodiaceae, Lamiaceae, Apiaceae, Scrophulariaceae and Polygonaceae) include 63.2% of species in newly formed habitats and 66.3% in pioneer plant communities. The family spectra of the pioneer vegetation classes were analyzed. The floristic proportions were established, which indicate that both floras are historically young and represent physical and geographical pecularities of the environmental conditions as well as high fluctuation activity of ecological processes. The aboriginal fraction was studied; it contains 560 species of 252 genera from 70 families. Similarity of the species composition of the newly formed habitats, coenofloras of the classes of pioneer vegetation and their aboriginal fractions has been analyzed according to Jaccard index.